Analisis determinan rendahnya pemberian ASI eksklusif di Desa Aluepade Kecamatan Kuala Batee Kabupaten Aceh Barat Daya - Nyakti Maisarah; Rika Andriani (Journal of Health and Therapy, 2024)
Breast milk (ASI) is the best food for babies because it contains complete nutrients to support optimal growth and development. However, although the WHO recommends exclusive breastfeeding for the first six months, many mothers still do not implement it optimally due to work factors, lack of support, low knowledge, cultural influences, and the promotion of formula milk. This study aims to determine the factors associated with low exclusive breastfeeding coverage in Aluepade Village, Kuala Batee District, Southwest Aceh Regency. The research design is descriptive, correlational, and cross-sectional, involving 35 breastfeeding mothers through a total sampling technique. Data were collected using a questionnaire from June 10 to July 13, 2024. The study results showed a significant association between low exclusive breastfeeding coverage and several factors, including age, education, employment, maternal health, knowledge, stress, support from health workers, and family support. It is hoped that health workers can increase motivation and educate mothers and families about the importance of exclusive breastfeeding for infant health.